Involvement of cAMP/EPAC/Akt signaling in the antiproteolytic effects of pentoxifylline on skeletal muscles of diabetic rats - Arcaro, Carlos Alberto [UNESP]; Assis, Renata Pires [UNESP]; Zanon, Neusa Maria; Paula-Gomes, Silvia; Carvalho Navegantes, Luiz Carlos; Kettelhut, Isis Carmo; Brunetti, Iguatemy Lourenco [UNESP]; Baviera, Amanda Martins [UNESP] (Amer Physiological Soc, 2018)
Advances in the knowledge of the mechanisms controlling protein breakdown in skeletal muscles have allowed the exploration of new options for treating muscle-wasting conditions. Pentoxifylline (PTX), a nonselective phosphodiesterase (PDE) inhibitor, attenuates the loss of muscle mass during catabolic conditions, mainly via inhibiting protein breakdown. The aim of this study was to explore the mechanisms by which PTX inhibits proteolysis in the soleus and extensor digitorum longus (EDL) muscles of streptozotocin-induced diabetic rats. The levels of atrogin-1 and muscle RING finger-1 were decreased, as were the activities of caspase-3 (EDL) and calpains (soleus and EDL), in diabetic rats treated with PTX, which at least partly explains the drop in the ubiquitin conjugate (EDL) levels and in proteasome activity (soleus and EDL). Treatment with PTX decreased PDE activity and increased cAMP content in muscles of diabetic rats; moreover, it also increased both the protein levels of exchange protein directly activated by cAMP (EPAC, a cAMP effector) and the phosphorylation of Akt. The loss of muscle mass was practically prevented in diabetic rats treated with PTX. These findings advance our understanding of the mechanisms underlying the antiproteolytic effects of PTX and suggest the use of PDE inhibitors as a strategy to activate cAMP signaling, which is emerging as a promising target for treating muscle mass loss during atrophic conditions. NEW & NOTEWORTHY cAMP signaling has been explored as a strategy to attenuate skeletal muscle atrophies. Therefore, in addition to beta(2)AR agonists, phosphodiesterase inhibitors such as pentoxifylline (PTX) can be an interesting option. This study advances the understanding of the mechanisms related to the antiproteolytic effects of PTX on skeletal muscles of diabetic rats, which involve the activation of both exchange protein directly activated by cAMP and Akt effectors, inhibiting the expression of atrogenes and calpain/caspase-3-proteolytic machinery.
Keywords: Akt; cAMP/EPAC signaling; pentoxifylline; skeletal muscle proteolysis; streptozotocin-diabetic rats